Peculiarities of vegetative homeostasis at children of early age with perinatal central nervous system damage - V. A. Zhelev; G. P. Filippov; D. V. Cherkashin; V. Yu. Serebrov; Ya. S. Pekker; Ye. V. Mikhalyov; L. V. Rassolova; M. G. Yelizarova; S. P. Yermolenko (Бюллетень сибирской медицины)
The aim of investigation was the study of vegetative homeostasis peculiarities at children of early age with perinatal central nervous system damage (PCNSD) during recovery. Method of computer cardiointervalometry has been used for the evaluation of vegetative homeostasis. Initial vegetative tone, vegetative reactivity, vegetative providing of activity and recovery time have been evaluated. 210 children (74 premature newborns with different stage of gestation and 136 full-term newborns) have been under supervision. The results of supervision show that with the increase of the PCNSD severity degree there is the increase of (i) the initial hypersympathicotonic vegetative tone, (ii) the insufficient vegetative providing of activity due to asthenic and astenosympathetic response for orthostatic load and (iii) the response of recovery time fatigue. These vegetative damages reflect the level of vegetative regulation of cardiac rate. The proposed method permits to reveal without bias the degree of vegetative nervous system damage and may be used for evaluation of the PCNSD severity degree and efficiency of applied therapy.